The great Boston molasses flood - Crandall, William, 1956-; Parnell, John A. (John Alan), 1964-; Spillan, John E. ([London] : SAGE, 2016)
This case discusses the Great Boston Molasses Flood of 1919, when a storage tanker split, releasing two million gallons of the liquid. Over twenty people were killed and hundreds of others injured in the disaster and it prompted a review of regulation concerning construction in the city.
Originally Published in: Crandall, W. R., Parnell, J. A., & Spillan, J. E. (2013). The Great Boston Molasses Flood. In Crisis management: Leading in the new strategy landscape (2nd ed., pp. 305-308). Los Angeles: SAGE Publications, Inc. ISBN: 9781412991681.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Industrial accidents -- Massachusetts -- Boston -- Case studies; Crisis management -- Case studies